Education as self-fulfilment and self-satisfaction - Victoria Donlevy; Barry van Driel; Cécile Hoareau McGrath (European Commission, Joint Research Centre (JRC), 2019)
Key drivers of contemporary rapid changes in the educational realm relate to ongoing technological, demographic, economic and social developments in modern European societies. These developments are having an impact on education throughout the lifespan, including a shift to a focus on new types of competences. This shift is becoming increasingly profound in a dynamic, multicultural, and interconnected Europe. The evidence, from various fields of research, shows that non-cognitive competences such as resilience, creativity, and empathy - as well as those noncognitive competences associated with social-emotional learning and active citizenship - have a positive impact on well-being and also performance. This paper takes a closer look at recent developments relating to these issues across the EU, both in terms of challenges and opportunities, and identifies practices that can serve as inspiration for future policies and practices. The paper reviews the literature as well as current practice related to trends, drivers, practices and future developments relating to four key sub-topics: non-cognitive competences as a broader topic; then resilience, creativity, and active citizenship as more specific sub-topics.
Keywords: 330; Education; Training; Non-Cognitive Competences; Resilience; Creativity; Active Citizenship; Wellbeing